MEMBANGUN KEMANDIRIAN SISWA AUTIS DI RUMAH AUTIS KOTA BANDUNG - Edy Suprianto Widyantoro; Ferdinandus Ngare; Mahardiansyah Suhadi (J-IKA : Jurnal Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas BSI Bandung, 2015)
ABSTRACTThe purpose of this research was: 1) to know the process of communication activities autistic students against teachers; 2) to know the contents of the message communication teachers against students; 3) to find out the language communication autistic students against teachers; 4) to find out how autistic student against teacher communication. His goal was to find out how autistic students teachers develop the independence that has been considered difficult to be able to become independent. This research uses the theoretical study of interpersonal communication with the application of the theory of symbolic interaction. The technique of data collection is carried out by means of direct obsrvasi and in-depth interviews. The research results indicate some of the factors important to communicate with an autistic student against whom a sense of comfort, an understanding of the needs, the patience and sincerity. Message communication in the form of a short customized command against an autistic student. The language used is verbal language are accompanied by nonverbal language. And the way its communication must be fun and done repeatedly.Keywords: Interpersonal Communication, An Autistic Child ABSTRAKTujuan penelitian ini adalah: 1) Untuk mengetahui proses kegiatan komunikasi guru terhadap siswa autis; 2) Untuk mengetahui isi pesan komunikasi guru terhadap siswa; 3) Untuk mengetahui bahasa komunikasi guru terhadap siswa autis; 4) Untuk mengetahui cara komunikasi guru terhadap siswa autis. Tujuannya untuk mengetahui bagaimana cara guru membangun kemandirian siswa autis yang selama ini dianggap sulit untuk bisa menjadi mandiri. Penelitian ini menggunakan kajian teoritis komunikasi interpersonal dengan penerapan teori interaksi simbolik. Teknik pengumpulan data dilakukan dengan cara wawancara mendalam dan obsrvasi langsung. Hasil penelitian menunjukan beberapa faktor penting untuk melakukan komunikasi terhadap siswa autis diantaranya rasa nyaman, pemahaman akan kebutuhan, kesabaran serta ketulusan. Isi pesan komunikasi berupa perintah singkat yang disesuaikan terhadap siswa autis. Bahasa yang digunakan adalah bahasa verbal yang disertai dengan bahasa nonverbal. Dan cara komunikasinya haruslah menyenangkan dan dilakukan secara berulang.Kata Kunci : Komunikasi Interpersonal, Anak Autis